Invariant natural killer T (iNKT) cell exhaustion in sarcoidosis. Issue 8 (25th June 2013) - Snyder‐Cappione, Jennifer E.; Nixon, Douglas F.; Chi, Joyce C.; Nguyen, Michelle‐Linh T.; Kirby, Christopher K.; Milush, Jeffrey M.; Koth, Laura L.
<x xml:space="preserve">Abstract</x> Invariant natural killer T (iNKT) cells are integral components of immune responses during many chronic diseases, yet their surface phenotypes, subset distribution, and polyfunctional capacity in this environment are largely unknown. Therefore, using flow cytometry, we determined iNKT cell phenotypic and functional characteristics in subjects with chronic inflammatory disease sarcoidosis and matched controls. We found that sarcoidosis subjects displayed lower iNKT‐cell frequencies, which correlated with lung fibrosis, C‐reactive protein levels, and other measures of clinical disease. The CD4−CD8− (double negative, DN) iNKT‐cell population was selectively lower in diseased individuals and the remaining DN iNKT cells exhibited higher frequencies of the activation markers CD69 and CD56. Functionally, both total IFN‐γ+ and the dual‐functional IFN‐γ+ TNF‐α+ iNKT cells were decreased in sarcoidosis subjects and these functional defects correlated with total iNKT‐cell circulating frequencies. As the loss of polyfunctionality can reflect functional exhaustion, we measured the surface antigens programmed death‐1 receptor and CD57 and found that levels inversely correlated with dual‐functional iNKT‐cell percentages. These findings reveal that, similar to traditional T cells, iNKT cells may also undergo functional exhaustion, and that circulating iNKT‐cell frequencies reflect these defects. Programmed death‐1 receptor antagonists may therefore be attractive therapeutic candidates for sarcoidosis and other iNKT‐cell‐mediated chronic diseases.